Visual Arts Learning Management Based on Local Potential at SMP Negeri 1 Bergas - Rizal Sofyana Fatahillah; Eko Sugiarto; Tjetjep Rohendi Rohidi (Universitas Muhammadiyah Enrekang, 2023)
Abstract Regional potential is a valuable resource in the development of Visual arts. One of the functions of education is as an effort to preserve the traditional nature of culture. Implementing arts education based on local potential requires good management. SMP Negeri 1 Bergas utilizes local potential in Semarang Regency as an object in creating paintings. The objectives of this research include: (1) Analyzing the role of local potential in Visual arts education, (2) understanding the management process and implementation of local potential-based Visual arts learning, and (3) identifying obstacles and opportunities. This research is qualitative research, using observation, interview and document study data acquisition methods. This research found that local potential can be utilized as a drawing object to train students' sensitivity to the environment. Art education management is carried out in the form of preparing lesson plans, implementing drawing lessons with teacher guidance from the sketching process to coloring, as well as providing feedback, to produce output in the form of drawing works. This learning is supported by qualified teachers and is hampered by limited costs and student discipline.. Keywords: Management, Learning, Drawing, Local Potential. Abstrak Potensi daerah merupakan sumber daya yang berharga dalam pengembangan seni rupa. Salah satu fungsi pendidikan adalah sebagai upaya pelestarian sifat tradisional kebudayaan. Pelaksanaan pendidikan seni berbasis potensi lokal ini memerlukan manajemen yang baik. SMP Negeri 1 Bergas memanfaatkan potensi, lokal yang ada di Kabupaten Semarang sebagai objek dalam berkarya seni lukis. Tujuan dari penelitian ini meliputi: (1) Menganalisis peran potensi lokal dalam pendidikan seni rupa, (2) mengetahui proses manajemen dan pelaksanaan pembelajaran seni rupa berbasis potensi lokal, serta (3) mengidentifikasi hambatan dan peluangnya. Penelitian ini merupakan penelitian kualitatif, dengan metode perolehan data observasi, wawancara, dan studi dokumen. PPenelitian ini menemukan fakta bahwa potensi lokal dapat dimanfaatkan sebagai objek menggambar untuk melatih kepekaan siswa terhadap lingkungan. Manajemen pendidikan seni dilaksanakan dengan berupa penyusunan RPP, pelaksanaan pembelajaran menggambar dengan bimbingan guru dari proses sketsa hingga pewarnaan, serta pemberian feedback, hingga menghasilkan output berupa karya gambar. Pembelajaran tersebut di dukung oleh guru yang mumpuni dan terhambat karena keterbatasan biaya dan kedisiplinan siswa. Kata Kunci: Manajemen, Pembelajaran, Menggambar, Potensi Lokal.